Expansion and enrichment of the semantic field of law as a way to create a legal society - Bratasyuk, Mariia; Rosolіak Oksana (Actual problems of law (Aktual’ni problemi pravoznavstva), 2020)
This article is devoted to the problem of formation of modern legal thinking, "meaningful thinking" in law, because it is thanks to such thinking that legal meanings are formed and real legal life becomes possible, legal reality is enriched and expanded. However, the reform of the intellectual component of legal reality in Ukraine is very slow, the semantic field of law is not only not enriched, but rather narrowed, which means that much of the social interaction can be removed and is already beyond the influence of law. This work is designed to show the need to expand and enrich the field of legal meanings in legal development, the role of meaningful legal thinking in the creation of legal reality. The article proves that in the context of the current legal development it is necessary to form a holistic integrative legal thinking, because it is in its bosom possible search and creation of legal meanings and their centers, around which the humanistic worldview is built. This is necessary for the modern Ukrainian state.